Hydrogen absorption by Zr-1Nb alloy with TiN[x] film deposited by filtered cathodic vacuum arc - Kashkarov E. B. Egor Borisovich; Nikitenkov N. N. Nikolai Nikolaevich; Syrtanov M. S. Maksim Sergeevich; Babihina M. N. (2016, 2016)
Title screen